Vliv podání kyseliny tranexamové na krevní ztráty po primární jednostranné náhradě kolenního kloubu - prospektivní studie - Pertlíček, J; Stehlík, J; Sadovský, P; Musil, D; Mezera, V (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2015)
PURPOSE OF THE STUDY: Tranexamic acid is an antifibrinolytic agent which blocks plasmin-mediated fibrin degradation. It is used in surgery to reduce intra-operative and post-operative blood loss. The aim of our study was to assess the effect of tranexamic acid administration on blood loss after elective primary unilateral total knee arthroplasty. MATERIAL AND METHODS: A total of 119 patients (50 men, 69 women) with an average age of 69.2 years were included. The patients were randomised into two groups: Group A received a single dose of tranexamic acid (Exacyl, 1.5 g i.v.) before the operation; Group B (control) did not receive any antifibrinolytic agent. All patients underwent surgery under spinal anaesthesia with a tourniquet applied to the operated leg. The intra-operative blood loss, post-operative blood loss based on drainage, pre- and post-operative levels of haemoglobin and haematocrit, and the number of administered blood transfusions were analysed. RESULTS: The administration of tranexamic acid led to a reduction in post-operative blood loss at all intervals tested, including the total blood loss (504 ± 214 vs 815 ± 231 ml; p < 0.001), and to reduced requirements for blood transfusion (1.18 ± 0.51 vs 1.54 ± 0.84 transfusion units; p < 0.05). A similar effect was observed in the subgroups of men and women; the total blood loss was higher in men than in women in both group B (non-significant) and group A (p < 0.05) patients. There was a gradual decline in haemoglobin and haematocrit levels during the post-operative period, with no significant differences between the two groups. Nor were there any differences in intra-operative blood losses either. No severe complications such as stroke, acute myocardial infarction or thromboembolic disease were recorded. DISCUSSION The administration of tranexamic acid before the application of a tourniquet resulted in reducing post-operative, but not intra-operative, blood losses in patients undergoing elective total knee arthroplasty. Transfusion requirements were reduced as well. CONCLUSIONS: Our study confirmed the efficacy and safety of tranexamic acid administration in relation to blood loss after total knee arthroplasty. In this indication, the administration is in accordance with the literature data.
Keywords: totální endoprotéza kolene; Blood Transfusion; Aged; Hemoglobins; antifibrinolytika; kyselina tranexamová; senioři; lidé; Sex Factors; Prospective Studies; hematokrit; Tranexamic Acid; prospektivní studie; hemoglobiny; Antifibrinolytic Agents; Arthroplasty, Replacement, Knee; Female; Hematocrit; Male; ženské pohlaví; sexuální faktory; krevní transfuze; Humans; mužské pohlaví; krvácení při operaci; Blood Loss, Surgical; Postoperative Hemorrhage; pooperační krvácení